Rapid method of cytology diagnosis by supravital staining in FNAC of various tissue and organs - Dr Rashmi Verma; Dr D.C. Gupta (Tropical Journal of Pathology and Microbiology, 2018)
Background: Supravital staining is the staining of living tissue removed from the body, but before cessation of the chemical life of the cells. Objective: The present study has been undertaken with the aim of to assess adequacy of material during FNAC, study the cytomorphological features and rapid diagnosis by wet smears. Also, to evaluate the diagnostic capability of supravital stain applied over the tissue obtained by FNAC of various organs and aspirated body fluids. Material and Method: In present study 100 fine needle aspiration of various tissue and organ were examined for cytological evaluation. FNAC were done in the Out Patients and In patients of several departments of Gajara Raja Medical College. Out of 100 cases 33 from lymphnode, 19 from soft tissue swelling, 13- from breast lump, 13 from thyroid, 04 from parotid swelling, 14 from the body fluid and 04 miscellaneous. Result:Out of 100 cases 93 cases (93%) were diagnosed correctly and discrepancy of 7 cases found in cytological diagnosis by toluidine blue and H&E stain. Out of 48 non-neoplastic cases 45 diagnosed correctly with the overall accuracy of 93.75% andout of 52 neoplastic cases 48 were diagnosed correctly with the accuracy of 92.30%. Discussion:The advantage of this technique is that cells are seen in living natural condition without any artefact caused by fixation, air dry or cutting.